2002
DOI: 10.1021/la0255166
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Rheological Study of a Bis-urea Based Reversible Polymer in an Apolar Solvent

Abstract: The structure of a bis-urea based reversible polymer is investigated using capillary viscosimetry, infrared spectroscopy, small-angle neutron scattering, and rheology. The highly viscoelastic solutions obtained in toluene are due to the formation of long and rigid fibrillar species. The cross section of these wires is measured and is shown to likely contain two or three molecules per axial repetition unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(184 citation statements)
references
References 19 publications
9
171
0
Order By: Relevance
“…6). [150][151][152] Note, that by protecting this hydrogen bonding synthon on each side in a hydrophobic pocket based on a C 11 aliphatic chain flanked with oligoethylene glycol chains, stable supramolecular polymers can also be obtained in water. 153 An alkylated derivative 2,4-bis(dibutylureido)-toluene (DBUT), is only able to form two hydrogen bonds per monomer and can be used as a chain stopper.…”
mentioning
confidence: 99%
“…6). [150][151][152] Note, that by protecting this hydrogen bonding synthon on each side in a hydrophobic pocket based on a C 11 aliphatic chain flanked with oligoethylene glycol chains, stable supramolecular polymers can also be obtained in water. 153 An alkylated derivative 2,4-bis(dibutylureido)-toluene (DBUT), is only able to form two hydrogen bonds per monomer and can be used as a chain stopper.…”
mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 At the concentration of the experiment (6 g/L), the interactions between objects can be neglected. 29 Therefore, the fit of the data was attempted with various form factors of rigid cylinders. The simplest one that can describe the whole data set is the form factor for a rigid cylinder with an elliptical cross-section and a uniform contrast.…”
Section: Page 11 Of 25 Langmuirmentioning
confidence: 99%
“…Furthermore, rheological measurements on samples of 2 at a concentration of 20 mg/ml demonstrated that the samples were true gels since the storage modulus (G') was greater than the loss modulus (G''), and both are independent of frequency in the linear viscoelastic regime tested. 22 The storage modulus of the gels (ca. 120 Pa) was of a similar magnitude to that of other metallosupramolecular polymer organogels reported in the literature (Fig.…”
Section: Supramolecular Self-assembly Of Ligand 1 and Of Its [2x2] Grmentioning
confidence: 99%